Corporate social disclosure by financial institutions in Malaysia: A preliminary study - Abdul Hamid, Fathilatul Zakimi; Ismail, Mohamad Sharofi; Abdul Rahman, Azhar (Institut Bank-Bank Malaysia, 2002)
THE IDEA OF corporate social disclosure (CSD)has been practised since practised since the 12th century (Guthrie and Parker, 1989 and Gray, 2000).Hackston and Milne (1996) define CSD as the provision of financial and non-financial information as stated in corporate annual reports or separate social reports.Gray et al (1995) remark that CDS embraces synonyms which include corporate and even social audit.On the other hand, Boyce (2000), quoting Estes (1976), defines social accounting as the communication of information concerning the impact of business activities on society, while environmental accounting has been defined as the communication of information concerning the impact of an entity's activity on the environment.The word 'impact' here means how much the environment employees, consumers, local communities and other interests are affected by business activities (Monks and Minow, 1995).There is an increasing demand from investors for social disclosure information.A study conducted in the UK by PricewaterhouseCoopers in June and July 1997 on institutional investors and financial analysts found that non-financial value drivers and qualitative information were relatively important in the disclosure of corporate information were relatively important in the disclosure of corporate information.These non-financial value drivers, among others, include CSD.Global Reporting Initiative (an international multi-stakeholder whose mission is to develop voluntary reporting in the area of economic, social and environmental disclosure) has developed a framework for corporate social reporting that businesses should disclose.The objective of this preliminary study is to identify the types of social information disclosed by Malaysian banks and finance companies in their annual reports.This study therefore concentrates on a specific sector (i.e. banking) in order to evaluate whether some specific pattern relating to disclosure exclude banks and financial institutions in their samples due to difference in regulations governing the financial services industry.foo and Tan, in a 1988 a study on social disclosure practice by public-listed companies in Malaysia and Singapore, found that banks and finance companies make the highest proportion of social disclosure as compared with other industries, However, they did not distinguish between Malaysian and Singapore banks.